Occurrence of torvoneustes (Crocodylomorpha, metrirhynchidae) in marine jurassic deposits of Oaxaca, Mexico - Barrientos-Lara, Jair Israel (2016)
Fil: Barrientos-Lara, Jair Israel. Universidad Nacional Autónoma de México. Instituto de Geología; México